Granular Materials 2017
DOI: 10.5772/intechopen.69196
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Dynamics of Granular Materials

Abstract: Granules are inelastic particles, undergoing dissipative and repulsive forces on contact. A granular state consists of a conglomeration of discrete, non-Brownian particles in a combined state of solid, liquid, and gas. Modern theoretical physics lacks general theories for the granular states. Simulation methods for particle dynamics include molecular dynamics (MD), Brownian dynamics (BD), Stokesian dynamics (SD), dissipative particle dynamics (DPD), and dissipative hydrodynamics (DHD). These conventional metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Dissipative hydrodynamics (DHD) has all the features required to be a universal simulation method for particle dynamics by taking specific advantages from MD, BD, SD, DPD, and DEM. A detailed review can be found elsewhere [14].…”
Section: Apply Constraint Forces To Form a Nonspherical Rigid Body Comentioning
confidence: 99%
See 3 more Smart Citations
“…Dissipative hydrodynamics (DHD) has all the features required to be a universal simulation method for particle dynamics by taking specific advantages from MD, BD, SD, DPD, and DEM. A detailed review can be found elsewhere [14].…”
Section: Apply Constraint Forces To Form a Nonspherical Rigid Body Comentioning
confidence: 99%
“…After an instantaneous collision, the two particle have the following velocities [14]: where 0 ≤ ε n ≤ 1 and À1 ≤ ε t ≤ 1 are restitution coefficients in the normal and tangential directions, respectively, μ ij is a reduced mass defined as…”
Section: Collision Rulesmentioning
confidence: 99%
See 2 more Smart Citations